Tomato plant inheritance of antixenotic resistance to tomato leafminer - Antônio, Adilson de Castro; da Silva, Derly José Henriques; Picanço, Marcelo Coutinho; Santos, Nerilson Terra; Fernandes, Maria Elisa de Sena (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to determine the inheritance of resistance by antixenosis in tomato plants (Lycopersicon esculentum) to tomato leafminer [Tuta absoluta (Lepidoptera: Gelechiidae)]. Evaluations were performed for tomato plants of the generations P1, P2, F1, F2, RC1 and RC2. The measured characteristic in the parents, BGH-1497 (P2 male) and 'Santa Clara' (P1 female), and in the F1, F2, RC1 and RC2 generations was the number of eggs per plant. This number was converted to the oviposition nonpreference index. The inheritance of antixenosis resistance of genotype BGH-1497 is ruled by a gene of greater effect and polygenes in epistatic interactions, with a phenotypic proportion of 13:3 between susceptible and resistant genotypes, respectively.